Detection of Second Mesiobuccal Canals in Maxillary First Molars Using a New Angle of Cone Beam Computed Tomography - (:unkn) unknown (KOWSAR PUBL, 2016)
Background: The localization of the additional canal orifice is one of the primary factors influencing the success of endodontic treatment. To deal with this problem, several techniques that each have their own advantages and disadvantages have been discussed in the literature. Objectives: The aim of the present in vitro study was to review a new approach to localizing second mesiobuccal (MB2) canals in maxillary first molars using cone beam computed tomography (CBCT). Patients and Methods: The CBCT scans of 296 patients who were referred to the department of dentomaxillofacial radiology were included in the study. The presence of MB2 canals, the angle formed by the mesiobuccal, distobuccal, and palatal root canal orifices (angle MDP), and the angle formed by the mesiobuccal, distobuccal, and MB2 canal orifices (angle MDMB2) were evaluated on the axial section. Pearson correlation and multiple linear regression methods were used for all predictions. All of the analyses were performed using SPSS for windows version 22.0. A two-sided P value < 0.05 was defined as statistically significant. Results: Of the 468 first molars, MB2 canals were observed in 296 subjects (141 females and 155 males). There were no statistically significant differences between females and males (P = 0.300). The angle MDP and angle MDMB2 were detected and evaluated. A moderate positive correlation was found between the angle MDPand the angle MDMB2. To predict the angle MDMB2 values, it was shown that the angle MDMB2 increased by 0.420 degrees when the angle MDP increased by 1 degree. If the angle MDP was greater than 90.95 degrees, there was a 78% probability that MB2 canals could be found. Conclusion: The determination of the presence of MB2 in the maxillary first molars may be carried out using CBCT scans. If the angle MDP was 91 degrees or greater, there was considered to be a higher probability that MB2 canals would be found in the endodontic cavity. Due to the positive correlation between the angle MDP and the angle MDMB2, the localization of MB2 canals may be easily performed in relation to the main MB canal.
Keywords: Cone Beam Computed Tomography; Root Canal Therapy; Endodontics; OPERATING MICROSCOPE; VOXEL SIZE; EX-VIVO; ROOT; MORPHOLOGY; CONFIGURATION; ANATOMY; RADIOGRAPHY; FREQUENCY; 1ST-MOLAR